Increased Serum Levels of miR-125b and miR-132 in Fragile X Syndrome: A Preliminary Study. (26th December 2022) - Couto, Rowena Rubim; Kubaski, Francyne; Siebert, Marina; Félix, Têmis Maria; Brusius-Facchin, Ana Carolina; Leistner-Segal, Sandra
Abstract : Background and Objectives: Fragile X syndrome (FXS) is a neurodevelopmental disorder, identified as the most common cause of hereditary intellectual disability and monogenic cause of autism spectrum disorders (ASDs), caused by the loss of fragile X mental retardation protein (FMRP). FMRP is an RNA-binding protein, a regulator of translation that plays an important role in neurodevelopment, and its loss causes cognitive and behavioral deficits. MicroRNAs (miRNAs) are small molecules that regulate gene expression in diverse biological processes. Previous studies found that the interaction of FMRP with miR-125b and miR-132 regulates the maturation and synaptic plasticity in animal models and miRNA dysregulation plays a role in the pathophysiology of FXS. The present study aimed to analyze the expression of miR-125b-5p and miR-132-3p in the serum of patients with FXS. Methods: The expressions of circulating miRNAs were studied in the serum of 10 patients with FXS and 20 controls using the real-time quantitative retrotranscribed method analyzed by relative quantification. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were generated to assess the diagnostic values of the miRNAs. Results: We found that both miR-125b and miR-132 were increased in the serum of patients with FXS compared with controls and likely involved with FMRP loss. The AUC (95% confidence interval) of miR-125b and miR-132 was 0.94 (0.86–1.0) and 0.89 (0.77–1.0), respectively. Databases allowed for the identification of possible target genes for miR-125b and miR-132, whose products play an important role in the homeostasis of the nervous system. Discussion: Our results indicate that serum miR-125b and miR-132 may serve as potential biomarkers for FXS. The increased expression of circulating miR-125b and miR-132 seems to be associated with the genotype of FXS. Predicted gene targets of the differentially regulated miRNAs are involved in cognitive performance and ASD phenotype. Classification of Evidence: This study provides Class III evidence that miR-125b and miR-132 distinguish men with FXS from normal controls.